A Companion to the Devil and Demons, c.1100-1750 - Edwards, Kathryn A. (Brill's Companions to the Christian Tradition, 2025)
For medieval and early modern Europeans, the Devil and his demonic minions were seen as increasingly active. They tempted monks, tortured the unwary, and conspired against humanity. They were responsible for waves of heresy, plague, famine, and religious division, and they formed unholy alliances foreshadowing the approaching Apocalypse and End Times. Bringing together eighteen internationally recognized specialists, A Companion to the Devil and Demons explores the latest research on premodern European beliefs about the Devil and demons. With chapters ranging from scholastic and necromantic perceptions of demons to the place of demons within witch trials, connections between demons and non-human beings, and media that spread ideas about demons, it argues for the centrality and durability of "demon knowledge" in European culture. Contributors to this volume: Philip C. Almond, Robin B. Barnes, Dean Phillip Bell, Michelle D. Brock, Fabián Alejandro Campagne, David J. Collins, SJ, Ismael del Olmo, Kathryn A. Edwards, Lizanne Henderson, David Johannes Olszynski, Richard Raiswell, Juanita Feros Ruys, James Sharpe, Julien Véronèse, Rita Voltmer, Hans de Waardt, Gary K. Waite, and Charles Zika.